1993
DOI: 10.1139/z93-059
|View full text |Cite
|
Sign up to set email alerts
|

Effets de la ration alimentaire, de la densité intraspécifique et des relations entre individus sur la croissance des juvéniles de l'espèce Nereis diversicolor (Annelida: Polychaeta)

Abstract: Requ le 2 1 janvier 1992 Accept6 le 17 septembre 1992 SCAPS, P., RETICRE, C., DESROSIERS, G., et MIRON, G. 1993. Effets de la ration alimentaire, de la densitk intraspkcifique et des relations entre individus sur la croissance des juvkniles de l'espkce Nereis diversicolor (Annelida : Polychaeta). Can. J. Zool. 71 : 424-430.L'klevage, en laboratoire, de juvkniles du Nereis diversicolor sur alimentation a base de Tetramin a permis de quantifier les effets des variations de la quantitk de nourriture, de la densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Studies undertaken by Esnault et al (1990) and Scaps et al (1993) ture were also found to induce negative effects on growth (Scaps et al, 1993). This study provides the first known account of the growth rates of juvenile D. aciculata and demonstrates the effect of density on growth rates, posterior segment condition and mortality when food is not limiting.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Studies undertaken by Esnault et al (1990) and Scaps et al (1993) ture were also found to induce negative effects on growth (Scaps et al, 1993). This study provides the first known account of the growth rates of juvenile D. aciculata and demonstrates the effect of density on growth rates, posterior segment condition and mortality when food is not limiting.…”
Section: Discussionsupporting
confidence: 55%
“…Competition for space has also been shown for Neanthes arenaceodentata, which exhibit aggressive behaviour at high density, as demonstrated by an increase in the frequency of polychaetes regenerating posterior segments (Bridges et al, 1996). Scaps et al (1993) recorded a reduction in growth and survival of lab-reared juveniles of Hediste diversicolor at high densities (3000/m 2 ), even in the presence of abundant food.…”
Section: Introduction Resumen: Crecimiento En Función De La Densidad mentioning
confidence: 85%
“…m −2 (high). The highest value was chosen as the maximum limit reported in literature for this species, above which not only growth rates but also survival capacity decrease (Scaps et al, 1993). The two lower values, similar to those recorded in natural populations of the Venice Lagoon (Maggiore and Keppel, 2007) might be both appropriate for a commercial farm system.…”
Section: Specific Experimental Conditions: Density Trialmentioning
confidence: 99%
“…In addition, it may also take the typical alimentary filter‐feeder behaviour, being able to select the particles trapped in the mucus which are subsequently passively conveyed to U‐ or Y‐shaped burrows by the water circulation (Harley, ; Vedel, Andersen & Riisgård, ). Various studies had already suggested that H. diversicolor might be a suitable species for aquaculture purpose, proving to be easy to breed in indoor systems and to exhibit several favourable physiological traits, such as high tolerance to a wide range of environmental parameters (salinity, temperature, substrate grain size) and rapid growth rates, at least when fed with commercial fish foods (Fidalgo e Costa, ; Fidalgo e Costa, Narciso & Cancela da Fonseca, ; Nesto, Simonini, Prevedelli & Da Ros, ; Scaps, Retiére, Desrosiers & Miron, ). Moreover, H. diversicolor may be a potentially high‐quality fatty acids source for reared fish and shrimp as it has been demonstrated that fat assimilation by ragworms reflects fat content of their diet (Santos et al., ).…”
Section: Introductionmentioning
confidence: 99%